Modeling and optimization of energy requirements of disc plough operation on loamy-sand soil in South-East Nigeria using response surface methodology - Okechukwu Oduma; Precious Ehiomogue; Chineze G. Okeke; Nkemdirim F. Orji; Elijah C. Ugwu; Muofunanya F. Umunna; Kenechi Nwosu-Obieogu (Scientific African, 2022)
Energy plays vital role in different in-field and post-harvest operations. It is the amount of fuel consumed during an operation. This research was conducted to model and optimize the energy requirements of disc plough on loamy-sand soil in South-East Nigeria using response surface methodology, to assist agriculturalists and operators of the plough to evaluate and probably decide on appropriate ploughing implement depending on the type of soil for their seed bed preparation for efficient production at negligible energy loss. The operational speed (5-9 kmh−1) and depth of cut (10-30 cm) were adopted as independent factors for the energy requirements study of the tillage implement. Results revealed that the highest fuel intake amount (energy requirement) of 31.25 lha−1 was recorded when the plough was operated at the depth of 30cm for the different speeds. The fuel consumption rate of the implement decreases by 49.98% when operating at cutting depth of 10 and 20cm irrespective of the working speed. The linear model equation was significant (P< 0.05) for the evaluation of energy requirements of the disc plough. The p-value of the model term was 0.0053 which entails that the model equation is significant. The linear model developed to predict the energy requirements of the plough with respect to the independent variables was expressed as Fcr = 3.61462 + 4.29641e−16Sp + 0.78100Dc. Where, Fcr is fuel intake rate, lha−1; Sp is operational speed, kmh−1 and Dc is cutting depth of the disc plough, cm. Results revealed that the coefficient of determination, R2 was 0.6500, which indicated good relationships among the variables, also an indication that the response (fuel intake rate) could describe 65% of the overall erraticism within the response. Result of simulation obtained revealed that the fuel consumption rate fall within the trial range. The predicted R2 (0.3129) was compatible with the adjusted R2 (0.5800) meaning that the investigational data fixed well. Finally, the optimum fuel consumption rate and the desirability of 20.51 lha−1 and 1.00 were respectively obtained at optimal operational speediness of 6.7 kmh−1 and ploughing depth of 18.56cm. In conclusion, cutting depth had greater influence on the energy requirement (fuel consumption rate) of the disc plough than the operational speed.